2018
DOI: 10.1016/j.jpsychires.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of vortioxetine versus agomelatine, categorized by previous treatment, in patients with major depressive disorder switched after an inadequate response

Abstract: This study has the ClinicalTrials.gov identifier NCT01488071.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Despite several compounds being approved for the treatment of MDD, roughly half of affected patients report an inadequate response to first‐line antidepressant treatment (Papakostas, Nielsen, Dragheim, & Tonnoir, 2018). Moreover, even though antidepressants represent the cornerstone in the treatment of MDD, available therapies often show several side effects (Rizvi & Kennedy, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several compounds being approved for the treatment of MDD, roughly half of affected patients report an inadequate response to first‐line antidepressant treatment (Papakostas, Nielsen, Dragheim, & Tonnoir, 2018). Moreover, even though antidepressants represent the cornerstone in the treatment of MDD, available therapies often show several side effects (Rizvi & Kennedy, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…New generations of antidepressants aim at optimizing treatment efficacy and tolerability. Vortioxetine, for instance, is a novel antidepressant with multimodal activity (Papakostas et al, 2018), approved for the treatment of MDD in the last decade in many countries worldwide (European Medicines Agency [EMA], 2014; Food and Drug Administration [FDA], 2013). Its mechanism of action combines the inhibition of the serotonin transporter and the direct modulation of serotonin (5‐HT) receptor activity, being it a 5‐HT1A receptor agonist, a 5‐HT1B receptor partial agonist, a 5‐HT3, a 5‐HT7, and a 5‐HT1D receptor antagonist and an inhibitor of the 5‐HT transporter (Bang‐Andersen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the STAR*D (Sequenced Treatment Alternatives to Relieve Depression) clinical trial indicated that fewer than 30% of depressive patients had a sufficient response to a single antidepressant (8) and that remission was lower in patients with two failed treatments (9). Approximately half of patients respond poorly to first-line antidepressant treatment (10). Moreover, current treatments often have side effects (11).…”
Section: Editorialmentioning
confidence: 99%
“…Several randomized, double-blind, placebo-controlled (RDBPC) studies of patients diagnosed with MDD have evaluated the efficacy of multiple vortioxetine doses (5,10,15, or 20 mg/day) for different short periods (6, 8, or 12 weeks). In most of these studies, drug-treated MDD patients showed significant improvement compared with a placebo (19,(28)(29)(30)(31)(32).…”
Section: Efficacy and Tolerability -Short-term Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation